Carbon Stocks Potential Above Ground Surface in Taman Hutan Raya Pancoran Mas, Depok - Al-Reza, Dimaz Danang; Hermawan, Rachmad; Prasetyo, Lilik Budi (Media Konservasi, 2017)
Global warming is the increase temperature of the atmosphere, ocean and terrestrial ecosystem that lead to global climate change. The global warming caused by the increase of atmospheric green house gases (GHGs), such as CO2, SOx, NOx and CH4. Deforestation will cause the increase of atmospheric GHGs, meanwhile reforestation will lowering atmospheric GHGs. In urban environment, Urban Open Space instead of enhance the aesthetical aspect of town, it also contribute to atmospheric carbon absorbtion through photosynthesis process and store the carbon in the form of biomass. The objectives of this research are to determine the potential of carbon stocks and analyze the relationship between LAI with potential carbon stocks in trees, Basal area, stand density at Tahura Pancoran Mas, Depok.  Biomass of trees and woody nekromass calculated based on allometric equations, the calculated carbon content of 47% of the biomass. Carbon stocks potential in Tahura Pancoran Mas, Depok was 33,92 Mg/ha or carbon stocks potential with an area of 6 ha was 203,52 Mg C. The result of regression analysis shows that a relationship between LAI with stand density has the strongest relationship than the other. Selected regression model to estimate LAI is the stand density = -10,2 + 227 LAI with R2 is 0.60 and has a value of accuracy is 12,08%. Keywords: carbon stocks, LAI, stand density